The Phenomenon of Code-Switching in Bilingual Preschool Settings: Its Role in First Language Acquisition Among Madurese-Indonesian Children - Ainur Rahman; Yuniatari Yuniaari; Renawati Renawati; Rosda Ayu Fitria; Khairunnisa Ulfadhilah; Ainur Rofiq Hafsi (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
Children in bilingual preschool environments, such as those found in Madurese-Indonesian communities, are frequently observed switching between their mother tongue and the national language in daily interactions, a phenomenon of code-switching that raises fundamental questions about whether such language alternation supports or hinders first language acquisition. This study addresses the central problem by examining the patterns and functions of code-switching among six children aged 4-6 years at TK ABA VIII Kamal, Bangkalan, and analyzing its role in their first-language acquisition process. The study aims to describe the patterns of code-switching that occur in interactions among six children aged 4-6 years in family and preschool settings, and to analyze the role of such code-switching in children’s first language acquisition. This study employs a qualitative case study approach. Data were collected through participant observation, recordings of natural speech, and in-depth interviews with parents and kindergarten educators in TK ABA VIII Kamal, Bangkalan. Data analysis was conducted using a descriptive-interpretive approach grounded in the code-switching typology of Gross et al. (2022), drawing on theories of language acquisition and sociolinguistics. The results indicate that code-switching in children’s daily interactions serves as a communicative strategy that strengthens first-language acquisition rather than hindering it. Code-switching plays a role in expanding vocabulary, reinforcing grammatical structures, and naturally fostering children’s metalinguistic awareness. These findings have important implications for preschool educators and Indonesian language teachers in designing learning strategies that are responsive to children’s linguistic backgrounds in bilingual regions.